2022
DOI: 10.3390/en15031198
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Economic Impact of Using Photovoltaic (PV) Energy for High-Efficiency Irrigation Systems: A Case Study

Abstract: This paper presents the results of a field study undertaken all over the Punjab, Pakistan, to evaluate the socio-economic and climatic impact of photovoltaic-operated high-efficiency irrigation systems (HEIS), i.e., drip and sprinkler irrigation systems. Nearly half of the rural population relies on agriculture for a living, and the recent energy crisis has had a negative impact on rural communities. Farmers’ reliance on fossil fuels for the operation of irrigation systems has increased exponentially, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
(35 reference statements)
3
8
0
Order By: Relevance
“…PV systems for operating drip-irrigation systems are more economically feasible than electric-and diesel-powered irrigation systems. This total cost per hour for electricity, diesel, and solar is similar to those found in the research study conducted by Raza et al [32].…”
Section: Comparison Of Pumping Systems Operating On Electricity Solar...supporting
confidence: 89%
See 2 more Smart Citations
“…PV systems for operating drip-irrigation systems are more economically feasible than electric-and diesel-powered irrigation systems. This total cost per hour for electricity, diesel, and solar is similar to those found in the research study conducted by Raza et al [32].…”
Section: Comparison Of Pumping Systems Operating On Electricity Solar...supporting
confidence: 89%
“…PV systems for operating drip-irrigation systems are more economically feasible than electric-and diesel-powered irrigation systems. This total cost per hour for electricity, diesel, and solar is similar to those found in the research study conducted by Raza et al [32]. PV systems for operating drip-irrigation systems are more economically feasible than electric-and diesel-powered irrigation systems.…”
Section: Comparison Of Pumping Systems Operating On Electricity Solar...supporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, the farms' sprinklers will be supplied by the stored water via gravity during low-renewable-power hours. In some studies, photovoltaic irrigation pumps are addressed as practical solutions to provide flexibility for both the power grid and farms [144].…”
Section: Agricultural Demand Flexibilitymentioning
confidence: 99%
“…Besides, SIF adoption impact analysis in the Philippines revealed that the adoption not only aided in GHG emissions reduction by up to 26.5 tons CO2eq/ha/year but also contributed to the energy sector by savings between 11.4 and 378.5 L/ha of diesel per year with an average of 315% returns on investment (Guno and Agaton, 2022). Furthermore, SIF adoption in Pakistan has significantly contributed to reducing operational costs, increased farmers' income, reduced 17,622 tons of CO2 emissions per year, and saved 41% of water usage (Raza et al, 2022). In addition, apart from irrigation purpose usage and meeting electricity needs, SIFs adoption contributes to facilitating drinking water requirements in water-scarce regions and contributes toward gender empowerment by alleviating the burden of labor-intensive diesel system operation and allowing women to utilize their time for productive purposes (IRENA, 2016;Agrawal and Jain, 2018).…”
mentioning
confidence: 99%